P23 Implementation of a specialist pneumonia intervention nurse (SPIN) service significantly improves outcomes for community acquired pneumonia (CAP) at a major nhs trust. (December 2018) - Free, RC; Richardson, M; Pillay, C; Skeemer, J; Hawkes, K; Gajjar, V; Broughton, R; Haldar, P; Woltmann, G
Abstract : Introduction: Influenza and pneumonia resulted in 2 69 313 emergency hospital admissions in the UK in 2016/2017, with the cost of treatment to the NHS estimated at £1 billion per year. University Hospitals Leicester NHS trust (UHL) dealt with 1 39 607 emergency admissions in 2017/2018. CAP is the leading cause of in-hospital mortality and contributes significantly to winter pressures experienced in recent years. Outcome is related to disease severity (CURB-65 score) and NICE (CG191) emphasises prompt management. We set up a SPIN (specialist pneumonia intervention nurse) service in 2013/2014 to assure prompt delivery of key interventions for CAP admissions. Aim was to raise awareness for healthcare staff and achieve a rapid clinical and radiological diagnosis of CAP including treatment guided by CURB-65. We report on the effectiveness of these nurse-led interventions and impact on crude/adjusted mortality. Methods: The SPIN service screens actively for CAP cases from admission lists. Confirmed cases are entered into a bespoke CAP database. Following a one-year implementation phase with intensive educational promotion we retrospectively compared a two-year baseline period (FY 2011/2012 – 2012/2013) with an intervention (period 2014/2015 – 2015/2016). Records were analysed for key interventions, length of stay (LOS), Charlson comorbidity index (CCI) and adjusted mortality. Results: 12, 490 CAP coded patients were admitted to UHL between FY 2011–2016 (table 1). Mean age was 72.4 (median=77), 51.4% were male. Between baseline and intervention periods the mean CCI rose and the mean LOS fell (table 1). Improved compliance with key CAP intervention factors was demonstrated with most interventions implemented in >90% of assessed admissions during the intervention period (table 2), crude and adjusted in-hospital mortality (HSMR) improved significantly (table 3). Mortality for admissions seen by the SPIN service was significantly lower compared to those not seen. Crude 30 day mortality was 12.2% in those individuals seen by the service, but 16.1% for those not seen (p<0.0001, OR=0.73). Conclusion: Consistent timely delivery of key interventions led by a specialist pneumonia intervention nursing (SPIN ) team is associated with significantly improved crude and adjusted mortality rates and may be an exemplar for improving the management of this common and serious condition.